Lipidomic Profiling Reveals the Reducing Lipid Accumulation Effect of Dietary Taurine in Groupers (Epinephelus coioides) - Bai, Fakai; Wang, Xuexi; Niu, Xingjian; Shen, Guiping; Ye, Jidan (Frontiers in Molecular Biosciences, 2021)
A lipidomic analysis was conducted to provide the first detailed overview of lipid molecules profiles in response to dietary lipid and taurine, and associations of liver lipid-lowering effect of dietary taurine with lipid molecular species and the positional distributions of fatty acids in the liver of juvenile orange-spotted grouper (Epinephelus coioides). The results indicated that liver was more sensitive to varied dietary lipid and taurine contents than muscle in regard to lipid molecules. A total of 131 differential lipid molecules (DLMs) were observed in the liver of grouper when dietary taurine was increased from 0 to 1% at 15% lipid, among which all the up- and down regulated DLMs are phospholipids (PLs) and triglycerides (TGs), respectively. The liver content of TGs containing 18:2n-6 attached at sn-2 and sn-3 positions on the glycerol backbone increased with increasing dietary lipid from 10% to 15% but decreased with increasing dietary taurine from 0 to 1%. Therefore, dietary taurine can not only reduce lipid accumulation through decreasing the contents of TGs containing 18:2n-6 at sn-2 and sn-3 positions, but also enhance the anti-inflammatory capacity and health status of grouper. This study will also provide a new insight into the function of taurine in farmed fish.